Cambio de función de restaurante/vivienda a centro lúdico y guardería geriátrica en Guayllabamba - Córdova Gordón, Jéssica Paulina (2015)
The elder usually is marginalized by society. Through a restructure of a space, the project has the plan to create geriatric care center. By creating a space where the elderly can spend the day in a more recreational way with care and most importantly a more dignified life. In recent years it has increased the need for centers where the elderly pass the morning with care and also in an environment that will be educational and be productive. This is why the new interior proposal space is going to be developed in a large, safe and with a very nice climate place for the elderly. The project is located in Guayllabamba, Ecuador, in an area easily accessible. The chosen site is 300 meters from the main road Simon Bolivar, there are currently three floors, on the ground floor initially was located a bar, that over time became a cellar. On the first floor a restaurant with typical Ecuadorian food and finally on the third floor an apartment for the owners. The project is purpose is to unify the spaces and create areas for different activities that older adults need to realize like physical therapy, mental therapy, manual therapy and various types of recreational activities. Because it is outside the city of Quito, the project is going to have a service offer door-to-door transportation from the city to the nursing home, and providing safety and comfort through the transport. The factor that set the tendency in the project design is “The Four Elements” the concept has very friendly shapes and colors for the user, by using this factor in the space they will feel very comfortable.